Repository application for the robotics club of the Technical University of Cotopaxi - Cadena, José (2023)
This work summarizes the design of an information repository developed for the robotics club (BOTS UTC) of the Technical University of Cotopaxi. The development phase of the application was presented. The development phase of the application was presented. The methods used and the importance of the tools used for the development of the program, creation of models, diagrams and BDD (database). The tools used for the development of the application were taken into account through the results obtained from a previous study carried out where various tools, methodologies, architectures, DBMS, and programming languages currently used by software development companies were selected. A description of the implementation, maintenance and testing phase corresponding to the waterfall model was developed, on which we based ourselves for the development of the project. Taking into account the proposed objective, this application was created to solve problems in the educational and social field, benefiting users with this proposal.